ANALISIS PERUBAHAN BUDAYA DAN LINGKUNGAN KERJA TERHADAP KOMITMEN DAN KINERJA KARYAWAN PT. BANK PEMBANGUNAN DAERAH JAWA TIMUR Tbk DI SURABAYA - Andriyan Fahmi Majid, Andriyan Fahmi Majid; I Dewa Ketut Raka Ardiana, I Dewa Ketut Raka Ardiana; Tri Andjarwati, Tri Andjarwati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
Business competition is increasingly fierce sticking out as a result of technological developments and globalization that requires all companies competing to create competitive advantage. This is done by the company in order to ensure the company's survival. It will be very difficult to continue to survive in business competition if the company is unable to adapt quickly. Every business entity is required to always make a transformation in facing various dynamics and business challenges. This study aims to prove and analyze the effect of variable cultural change on employee commitment, cultural change on employee performance, work environment on employee commitment, work environment on employee performance, and employee commitment to employee performance. The sample used was 225 respondents who were employees of PT. Bank Pembangunan Daerah Jawa Timur Tbk. Data analysis using SEM AMOS version 24. Based on the analysis results it was concluded that culture change (X1) influences employee commitment (Z), culture change (X1) affects employee performance (Y), work environment (X2) affects employee commitment (Z), work environment (X2) affect employee performance (Y), and employee commitment (Z) affect employee performance (Y).